2024
DOI: 10.3390/land13010060
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Rural Revitalization Effect under the Interaction of Agro-Tourism Integration and Tourism-Driven Poverty Reduction: Empirical Evidence for China

Debin Ma,
Dongqi Sun,
Ziyi Wang

Abstract: Under the robust impetus of China’s rural revitalization strategy, agro-tourism integration and tourism-driven poverty reduction have profoundly impacted various aspects of China’s economy, society, and ecology. This has propelled coordinated urban–rural development and the sustainable development of the tourism industry. This study introduces an analytical framework encompassing tourism-driven poverty reduction, agro-tourism integration, and rural revitalization. Through PVAR and threshold models, it empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The comparison results raise a question: why do rural areas with weaker infrastructure and transportation tend to have higher prices for similar B&Bs than cities? Through existing research on rural tourism and an in-depth understanding of the rural environment and consumer psychology [59,60], it has been found that when rural B&Bs are offered to tourists at a price higher than the accommodation conditions of similar products and services in the city, tourists actually pay for the added value of rural natural landscapes to such tertiary industry spaces. It can also be said to be an ecological premium.…”
Section: Value Performancementioning
confidence: 99%
“…The comparison results raise a question: why do rural areas with weaker infrastructure and transportation tend to have higher prices for similar B&Bs than cities? Through existing research on rural tourism and an in-depth understanding of the rural environment and consumer psychology [59,60], it has been found that when rural B&Bs are offered to tourists at a price higher than the accommodation conditions of similar products and services in the city, tourists actually pay for the added value of rural natural landscapes to such tertiary industry spaces. It can also be said to be an ecological premium.…”
Section: Value Performancementioning
confidence: 99%
“…At the same time, when constructing a multidimensional poverty and tourism development indicator system, more effective and reliable indicators should be selected based on more regional empirical research to provide a more in-depth evaluation. Considering the complexity of the poverty reduction effect of tourism, a theoretical model of the mechanism of action can be constructed for pre-analysis [55] in combination with the requirements of consolidating poverty alleviation achievements and rural revitalization. On this basis, the robustness and reliability of the model can be further improved through the adjustment and optimization of time series, coverage area, and sample selection.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Tourism investment has a significant impact on land-use changes (Yasemin Sarıkaya Levent et al, 2024), leading to the conversion of agricultural and forest land into golf courses, leisure parks, or shopping malls, with negative consequences for local livelihoods and biodiversity (Mattah et al, 2024). The construction of tourism infrastructure potentially leads to habitat fragmentation and a loss of ecological connectivity, which may affect the survival of certain animal and plant species (Ma et al, 2024). However, tourism investment can also help to protect the environment and conserve natural landscapes, particularly in areas threatened by unregulated development or unsustainable economic activities.…”
Section: Introductionmentioning
confidence: 99%